Support leg joint kinetic determinants of maximal speed sprint performance - Nagahara, R.; Murata, M. (Journal of Sports Sciences, 2024)
This study aimed to comprehensively demonstrate support leg joint kinetic determinants of maximal speed sprint performance. Ground reaction forces and marker coordinates attached to the body were measured in the maximal speed phase from 44 male sprinters. Then, three-dimensional leg joint torque, angular velocity and power were calculated. Greater maximal running speed (9.47 ± 0.32 m/s) was correlated with greater mean hip extension (r = 0.354, p = 0.018) and flexion (r = -0.322, p = 0.033) and ankle plantar flexion torques (r = 0.464, p = 0.002), as well as greater ankle plantar flexion torque from 30% to 70% of the support phase (p < 0.001). Greater maximal running speed was associated with greater mean hip extension (r = 0.386, p = 0.010) and smaller knee extension velocities (r = -0.426, p = 0.004). Regarding joint torque power, greater maximal running speed was associated with greater mean positive (r = 0.416, p = 0.005) and negative (r = -0.390, p = 0.009) hip flexion - extension powers and positive (r = 0.642, p < 0.001) and negative (r = -0.512, p < 0.001) ankle plantar - dorsi flexion powers. Moreover, greater maximal speed was correlated with greater positive and negative ankle plantar - dorsi flexion powers from 21% to 39% (p < 0.001) and from 56% to 80% (p < 0.001), respectively, during the support phase. Understanding the joint kinetics related to maximal running speed will improve technical considerations and strength training direction for sprinters.